A Nonuniformity Correction Method Based on Gradient Scene Calibration. Issue 5 (April 2020) - Liu, Rang; Tong, Yan; Ma, Pufang; Zhao, Yafei; Zhao, Yanjie
Abstract: The nonuniformity of infrared focal plane array (IRFPA) seriously affects the image quality and the measurement accuracy of the infrared imaging system. The two-point nonuniformity correction (NUC) method based on blackbody calibration performs a less than very satisfactory result to correct the sky scene with gradient gray distribution. Aiming at this problem, a new NUC method based on gradient scene calibration is proposed. First, the correction models are deduced in theory with the reference of the blackbody and the gradient scene. Then the pure sky images at the two different pitch angles are used as two reference temperature points to obtain the gain and offset coefficients by two-point correction. Next, two correction coefficients are filtered to remove residual noise. Finally, an outfield experiment with the proof-of-concept camera is performed. Experimental results show that the signal-to-noise ratio (SNR) of the point target image corrected by the proposed method is increased from 5.56 to 9.84 compared with the blackbody calibration-based NUC. And it has the preference of low complexity and easy implementation in the real-time system.